Fundamental statistics for the behavioral sciences - Howell, David C. (Wadsworth, Cencage Learning, 2014)
Focuses on providing the context of statistics in behavioral research, while emphasizing the importance of looking at data before jumping into a test. This title provides students with an understanding of the logic behind the statistics, so they understand why and how certain methods are used-rather than simply carry out techniques by rote